Raman sideband cooling in optical tweezer arrays for Rydberg dressing - Nikolaus Lorenz, Lorenzo Festa, Lea-Marina Steinert, Christian Gross (SciPost Physics, 2021)
Single neutral atoms trapped in optical tweezers and laser-coupled to Rydberg states provide a fast and flexible platform to generate configurable atomic arrays for quantum simulation. The platform is especially suited to study quantum spin systems in various geometries. However, for experiments requiring continuous trapping, inhomogeneous light shifts induced by the trapping potential and temperature broadening impose severe limitations. Here we show how Raman sideband cooling allows one to overcome those limitations, thus, preparing the stage for Rydberg dressing in tweezer arrays.